Asymmetric electrophilic fluorocyclization with carbon nucleophiles. - Wolstenhulme, JR; Rosenqvist, J; Lozano, O; Ilupeju, J; Wurz, N; Engle, K; Pidgeon, G; Moore, P; Sandford, G; Gouverneur, V (2013)
Twist of 'F'ate: Various helical-shaped fluorinated tetracyclic molecules were prepared by fluorocarbocyclization of prochiral alkenes. The development of a new class of chiral Selectfluor (1) proved instrumental in developing an asymmetric variant of this transformation. These novel chiral N-F reagents are readily accessible by fluorine transfer from shelf-stable N-fluoropyridinium salts. Copyright © 2013 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.